Liquid biopsy in prostate cancer: A novel dual biomarker analysis approach integrating circulating tumor cells and circulating tumor DNA data: Dual biomarker analysis in prostate cancer via liquid biopsy - Li, Qianyue; Tang, Lei; Zhao, Yawei; Li, Zhikun; Ma, Wang; Ma, Liujiang (Cellular and Molecular Biology, 2024)
This study aimed to explore the potential of liquid biopsy as a diagnostic tool by integrating two key biomarkers, Circulating Tumor Cells (CTCs) and Circulating Tumor DNA (ctDNA), and to enhance the detection fidelity of prostate cancer. A dual biomarker analysis approach was employed to synergize the sensitivities of CTCs and ctDNA. Various genetic mutations of ctDNA and tissues were scrutinized, investigating their prevalence, co-existence, and mutual exclusivity. The findings uncovered a more intricate mutation landscape than previously anticipated, indicating a complex interplay between cellular and genetic aberrations in prostate cancer. Through harnessing the combined power of CTCs and ctDNA, our dual biomarker approach provides a more comprehensive understanding of prostate cancer genetics. This has the potential to revolutionize early detection and guide personalized therapeutic interventions.